Volcano-tectonic deformation in the Kivu Region, Central Africa: Results from six years of continuous GNSS observations of the Kivu Geodetic Network (KivuGNet). (October 2017) - Geirsson, Halldor; d'Oreye, Nicolas; Mashagiro, Niche; Syauswa, Muhindo; Celli, Gilles; Kadufu, Benjamin; Smets, Benoît; Kervyn, François
Abstract: We present an overview of the installation, operation, and initial results of the 15-station KivuGNet (Kivu Geodetic Network) in the Kivu Region, Central Africa. The network serves primarily as a research and monitoring tool for active volcanic, earthquake, and plate boundary processes in the region. Continuous operation of in-situ measurement networks in naturally and politically harsh environments is challenging, but has proven fruitful in this case. During the operation of the network since 2009, KivuGNet has captured: co-eruptive deformation from two eruptions of Nyamulagira (in 2010 and 2011–2012); inter-eruptive deformation, which we interpret as a combination of plate motion across the Western – East Africa Rift, and decreasing deep-seated magma accumulation under the Nyiragongo-Nyamulagira region; co-seismic deformation from the Mw 5.8 August 7, 2015 Lwiro earthquake at the western border of Lake Kivu. We hope that this study will serve as a motivation for further implementation of in-situ geodetic networks in under-monitored and under-studied sections of the East African Rift. Highlights: A continuous GNSS network of 15 stations is operating in the Kivu Region. We record both inter-eruptive and co-eruptive deformation from Nyamulagira and Nyiragongo. Current deformation indicates ongoing magma accumulation at Nyamulagira-Nyiragongo.